OC-088 Prospective Pilot Study to Investigate Transcutaneous Sacral Nerve Stimulation for Faecal Incontinence. (4th June 2013) - Thomas, G; Norton, C; Nicholls, R J; Vaizey, C
Abstract : Introduction: Sacral nerve stimulation (SNS) is an effective treatment for faecal incontinence (FI). However it is expensive, it requires two operations and has a risk of infection, implant migration and pain. Transcutaneous SNS is non-invasive and cheap. Only one small study has previously reported its use for FI. The aim of this study is to further assess the efficacy of transcutaneous SNS for FI. Methods: Recruited patients self-administered transcutaneous SNS for 12 hours a day, over four weeks. A two week bowel diary was kept for the final two weeks and compared to baseline. St Marks FI scores, a visual analogue scale assessing satisfaction with bowel habit, Rockwood FI QOL scores and SF-36 QOL scores were obtained. Results: Ten patients were recruited. Two achieved complete continence. There were significant reductions in the frequency of FI episodes per week, 9.5 (7.5) to 3 (7.38); p = 0.03, and in the frequency of defecation per week, 25.5 (19.5) to 14.5 (14.9); p = 0.007. There was a significant improvement in the ability to defer defecation (1(1.25) to 4.5 (4.5) minutes, p = 0.02). There was a significant improvement in the St Marks FI score, 20 (5.25) to 14.5 (8.0); p = 0.01. There was a significant improvement in the bowel habit satisfaction visual analogue scale 8.5 (20) to 45 (33); p = 0.008. There were no significant changes in the Rockwood FI QOL score, or in the SF-36 QOL score. No complications were reported. Conclusion: Transcutaneous SNS appears to be an effective and safe treatment for FI. Disclosure of Interest: None Declared